Collaborative Governance and Employee Engagement in Cross Sector Organizations: Evidence from East Java - Grace Carolina Malau; Tz-Li Wang; Yahya Fikri (Global Review of Tourism and Social Sciences, 2026)
This study investigates how collaborative governance quality influences employee engagement and perceived collaborative performance through collaborative leadership, role clarity across organizations, and inter-organizational trust. The study adopts a quantitative, cross-sectional survey design. Data were collected from 332 government employees involved in inter-organizational collaboration across provincial and district-level government organizations in East Java between March and May 2025. The proposed research model was tested using Partial Least Squares Structural Equation Modeling to examine direct and mediating relationships among the constructs. The findings show that collaborative governance quality has a strong positive effect on collaborative leadership and significant indirect effects on role clarity and inter-organizational trust. Collaborative leadership significantly enhances both role clarity and trust, which in turn positively influence employee engagement. Employee engagement emerges as the most proximate and powerful predictor of perceived collaborative performance. Mediation analysis indicates that governance quality affects engagement and performance primarily through leadership, role clarity, and trust rather than through direct effects. This study extends collaborative governance theory by integrating leadership and human resource management perspectives, offering a micro-level explanation of how governance arrangements shape employee engagement and performance.